Immunization route-mediated differences in long-term maturation of humoral immune response induced by adenovirus vector-based COVID-19 vaccine Sputnik V in nonhuman primates - Tukhvatulin, Amir I.; Gordeychuk, Ilya V.; Dzharullaeva, Alina S.; Dolzhikova, Inna V.; Bayurova, Ekaterina O.; Izhaeva, Fatima M.; Kovyrshina, Anna V.; Zhitkevich, Alla S.; Avdoshina, Daria V.; Gulyaev, Stanislav A.; Gulyaeva, Tatiana V.; Moroz, Andrey V.; et al. (Frontiers in Immunology, 2025)
IntroductionOn the background of kaleidoscopic changes of SARS-CoV-2 circulating variants, constant presence of SARS-CoV-2 in the human population hampers the dissection of native long-term immunogenicity of COVID-19 vaccines.MethodsFor this purpose, we performed a more than two-year-long evaluation of parameters of the humoral immune response elicited by intramuscularly (IM) and intranasally (IN) delivered adenovirus vector-based Sputnik V vaccine in nonhuman primates (NHP, Common marmosets), which are naturally nonsusceptible for SARS-CoV-2 infection.ResultsAlthough both immunization routes elicited prominent humoral immune responses in a short-term perspective, the long-term kinetics significantly differed between the IM and IN groups. While the titers of local and systemic antigen-specific antibodies (both IgA and IgG) nearly disappeared within two years upon IN vaccination, IM vaccination led to the highest IgG values in nasal swabs as well as IgA and IgG in serum specimens from NHPs by the end of observation period (day 764). Unlike IN vaccination, IM vaccination also resulted in a continuous long-term increase in serum maturation parameters such as antibody avidity, neutralization potency and breadth.DiscussionThe present study provides valuable information about distinct features of the long-term postvaccination humoral immune response in nonhuman primates induced by adenoviral COVID-19 vaccine administered by the intramuscular and intranasal routes commonly used in clinical practice.